What Drives Corporate Social Responsibility? Institutional Analysis of CSR in South Korean Context - Jung, Se Woo (2013)
This dissertation seeks to explore the CSR drivers and to identify the social meaning of CSR in South Korea. To succeed in its aim, the dissertation will employ the institutional theory because it provides a framework of analysing various social aspects. Also, corporate citizenship theory is applied to discuss the role of government and an effect of globalisation as a key CSR driver. This paper defines globalisation in the South Korean context and how that benefits to the society. Further, to recognise where Korean CSR positions in the global context, it takes general comparison on CSR governance system with UK. The research draws on a qualitative approach to explore socially constructed meaning of CSR in South Korea by a method of interview and document analysis.